The Cart before the Horse: When Cognitive Neuroscience Precedes Cognitive Neuropsychology - Agis, Daniel (Cogn Neuropsychol, 2017)
Cognitive Neuropsychology (CN) has had an immense impact on the understanding of the normal cognitive processes underlying reading, spelling, spoken language comprehension and production, spatial attention, memory, visual perception, and orchestration of actions, through detailed analysis of behavioral performance by neurologically impaired individuals. However, there are other domains of cognition and communication that have rarely been investigated with this approach. Many cognitive neuropsychologists have extended their work in language, perception, or attention by turning to functional neuroimaging or lesion-symptom mapping to identify the neural mechanisms underlying the cognitive mechanisms they have identified. Another approach to extending one’s research in CN is to apply the methodology to other cognitive functions. We briefly review the domains evaluated using methods of CN to develop cognitive architectures and computational models and the domains that have used functional neuroimaging and other brain mapping approaches in healthy controls to identify the neural substrates involved in cognitive tasks, over the past 20 years. We argue that in some domains, neuroimaging studies have preceded the careful analysis of the cognitive processes underlying tasks that are studied, with the consequence that results are difficult to interpret. We use this analysis as the basis for discussing opportunities for expanding the field.